Plaut-vincent stomatitis: A case report - ÜNAL, SUAY YAĞMUR; KESER, GAYE; NAMDAR PEKİNER, FİLİZ MEDİHA (My University, 2023)
Necrotizing ulcerative stomatitis or Plaut-Vincent’s Stomatitis is a complication of necrotizing ulcerative gingivitis that extends beyond the gingiva and is involved in other parts of the oral mucosa, with Fusiform bacillus, Borrelia vincenti and other anaerobic microorganisms being the most common associated bacteria. It starts with sore throat, bad smell in the mouth, bleeding gums in young adults with poor oral hygiene and decreased immune resistance. In this case, clinical findings of Plaut-Vincent Stomatitis belonging to a male patient are presented. In a 22-yearold male patient, erythematous, ulcers with irregular margins and grayish-white fibrin were observed in the soft tissue of the right third molar region of the mandible and in the buccal mucosa. The patient has halitosis, difficulty in swallowing, pain in the oropharynx, and lymphadenopathy. In the treatment of infected tissues, improvement was observed after systemic antibiotics and hydrogen peroxide mouthwash were applied for 6-7 days. PlautVincent Stomatitis is frequently seen in young adults and poor oral hygiene, smoking, emotional stress, alcohol consumption and malnutrition are stated as etiological factors that predispose to this disease. Detection of ulcerated lesions in soft tissue examination is important in diagnosis and treatment.

Nekrotizan ülseratif stomatitis ya da Plaut – Vincent Stomatitisi nekrotizan ülseratif gingivitisin bir komplikasyonu olup gingivanın ötesine uzanarak oral mukozanın diğer bölgelerinde tutulum gösteren, Fusiform basillus, Borrelia vincenti ve diğer anaerobik mikroorganizmaların en yaygın ilişkili bakteriler olduğu tablodur. Ağız hijyeni iyi olmayan, immün direnci düşmüş genç erişkinlerde, boğaz ağrısı, ağızda kötü koku, dişeti kanamasıyla başlar. Bu olguda erkek hastaya ait Plaut – Vincent Stomatitisi klinik bulguları sunulmaktadır. 22 yaşında erkek hastada mandibula sağ üçüncü molar bölge yumuşak dokuda ve bukkal mukozada eritemli, ülserlerle birlikte düzensiz marjinler ve kirli beyaz, grimsi fibrin izlenmiştir. Hastada halitozis, yutkunmada zorluk, orofarenkste ağrı ve lenfadenopati mecvuttur. Enfekte dokuların tedavisinde 6-7 gün süreyle sistemik antibiyotik ve hidrojen peroksitli gargara uygulandıktan sonra iyileşme gözlenmiştir. Sıklıkla genç erişkinlerde görülmekle birlikte kötü ağız hijyeni, sigara, duygusal stres, alkol tüketimi ve yetersiz beslenme bu hastalığa zemin hazırlayan etiyolojik faktörler olarak belirtilmektedir. Hastalarda yumuşak doku muayenesinde ülsere lezyonların tespit edilmesi, tanı ve tedavide önem taşımaktadır
Plaut-vincent stomatitis: Bir olgu sunumu
Keywords: Diş Hekimliği; Klinik Bilimler; Oral Diagnoz ve Radyoloji; Sağlık Bilimleri; Dentistry; Clinical Sciences; Oral Diagnosis and Radiology; Health Sciences; Klinik Tıp (MED); Klinik Tıp; DİŞ HEKİMLİĞİ, ORAL CERRAHİ VE TIP; Clinical Medicine (MED); CLINICAL MEDICINE; DENTISTRY, ORAL SURGERY & MEDICINE; Periodontoloji; Ortodonti; Ağız Cerrahisi; Diş Hijyeni; Dişçilik Hizmetleri; Diş Hekimliği (çeşitli); Periodontics; Orthodontics; Oral Surgery; Dental Hygiene; Dental Assisting; Dentistry (miscellaneous); General Dentistry; Necrotizing ulcerative stomatitis; Plaut-Vincent Stomatitis; Third molar; Oral Diagnosis; Treatment; Nekrotizan Ülseratif Gingivitis; PlautVincent Stomatiti; 3.Molar Diş; Oral Diagnoz; Tedavi